Ionic conductivity and dielectric study of sodium iodide-sodium dicyanamide solid electrolyte / Mohd Khairul Hazwan Yusof and Azizah Hanom Ahmad - Yusof, Mohd Khairul Hazwan; Ahmad, Azizah Hanom (2017)
Sodium solid electrolyte based on sodium dicyanamide, NaN(CN)2 doped with sodium iodide, NaI was prepared by ultra-fined grinding using planetary milling and pelletised with pellet press. Electrical conductivity and dielectric permittivity study were carried out by Electrochemical impedance spectroscopy (EIS) at frequency range between 50 Hz to 5.00 x 106 Hz. Highest conducting sample at room temperature condition managed to achieved by optimizing the doped sodium salt content with weight composition of 10NaI-90NaN(CN)2 with ionic conductivity value of (5.67 ± 1.26) x 10-4 S cm-1 at ambient temperature condition. The findings are further supported with 10 wt.% NaI in solid electrolyte system sample possessed highest dielectric constant and dielectric loss values at lower frequency region that showed non-Debye behavior for charge storage. Transference number measurement were performed and obtained a value of 0.96 that confirmed the sodium solid electrolyte sample is ionic conductor in nature.